Population structure of Indian mackerel (Rastrelliger kanagurta) in Java and Bali Island, Indonesia inferred from otolith shape - Arief Wujdi,; Han, Ju Kim; Chul, Woong Oh (Penerbit Universiti Kebangsaan Malaysia, 2022)
The Indian mackerel, Rastrelliger kanagurta, is a commercially important resource across Indonesia’s archipelagic waters. Despite its essential role in the fisheries industry, information regarding its population structures for management purposes is still limited. The present study investigates the variability of otolith shape as an efficient tool for stock discrimination. A total of 159 pairs of sagittal otolith were sampled at four localities along the southern Java-Bali coastal waters. Otolith outline was modeled by using Wavelet coefficients and was compared between localities using ANOVA-like permutation test, Canonical Analysis of Principal Coordinates (CAP), and classification test performed using linear discriminant analysis. The results showed significant differences in the shape of otolith between populations, reflected explicitly in the morphological feature of the excisura major. The differences in otolith shape were examined from all localities (ANOVA-like, p<0.001, and CAP p>0.05), except those otoliths between Palabuhanratu and Pacitan, thus, a mixed stock may occur in these two locations. These findings were also confirmed by the low classification success rate using LDA 44.26%. These results suggested that at least two distinct stocks potentially contributed to the fishery, impacting species management and conservation.